Review of Traumatic Duodenal Injuries: Etiology, Diagnosis, and Management. Issue 5 (May 2023) - Diggs, Laurence P.; Gregory, Stephanie; Choron, Rachel L.
Traumatic duodenal injuries are rare and often challenging to diagnose and treat. Management of these injuries remains controversial and continues to evolve. Here, we performed a review of the literature and guidelines for the diagnosis and management of traumatic duodenal injuries. A common recommendation in more recent literature is primary, tension-free repair of duodenal injuries when possible if surgical repair is necessary. Conversely, if duodenal injuries are unamenable to primary repair, more complex procedures such as Roux-en-Y duodenojejunostomy or pancreaticoduodenectomy may be necessary. Regardless of injury grade or type of surgical repair, the literature continues to support wide extraluminal drainage. Over time, the management of complex duodenal injuries has evolved to favor simple primary repair whenever possible. According to recent studies, more complex procedures are associated with higher rates of post-operative complications and should be reserved for severe injuries when primary repair is not possible.